(untitled) (Sebha University Conference Proceedings, 2022)
This study deals with the issue of administrative and financial corruption factors, its causes and treatment as an applied study on the branches of Jumhouria Bank in Sebha. The study relied on a random sample of the study population, represented by the employees of the Jumhouria Bank branch in Sebha, where a questionnaire sheet was distributed for this purpose, and the researchers used the statistical analysis program (SPSS) to analyze the data obtained from the study sample. The study reached a set of results, including that the sample members look at administrative and financial corruption alike, and the difference in gender, educational qualification, work experience, age, and job level has no effect on their opinions about financial and administrative corruption, and poor economic conditions helps the existence of financial corruption. And administrative in the branches of the Jumhouria Bank in Sebha, and that the lack of clarity of the laws and legislation in force and the internal regulations in force in the state and the bank represent an important aspect in the spread of administrative and financial corruption.